Ten-year follow-up of the 'minimal MRI lesion' subgroup from the original CHAMPS Multiple Sclerosis Prevention Trial. (April 2015) - Simon, JH; Kinkel, RP; Kollman, C; O'Connor, P; Fisher, E; You, X; Hyde, R; ,
Background: Patients with clinically isolated syndrome (CIS) and characteristic magnetic resonance imaging (MRI) lesions are at high risk for multiple sclerosis (MS). However, patients with a minimal MRI lesion burden (a low T2-hyperintense [low T2] lesion count) may have borderline formal diagnostic criteria, presenting a clinical management challenge. Objective: Compare the 10-year disease progression of patients with low and higher T2 lesion counts treated over most intervals. Methods: CIS patients from the original CHAMPS MS trial were retrospectively assigned to low-T2 (first quartile; 2–8 lesions) or higher-T2 (second through fourth quartiles; ≥ 9 lesions) groups using baseline T2 lesion counts. The 5- and 10-year open-label extension of CHAMPS (CHAMPIONS) evaluated conversion to clinically definite MS (CDMS), MRI activity, relapses, and disability. Results: The vast majority of patients showed new disease activity by MRI and/or clinical criteria at 10 years (low-T2 86%; higher-T2 98%). Fewer low-T2 than higher-T2 patients developed CDMS (40% vs. 63%; p = 0.013); low-T2 patients also had fewer new brain lesions, less brain volume loss, and less disability progression. Conclusion: CIS patients with low T2 lesion counts show continued disease activity. However, all assessments of disease progression over 10 years indicated a significantly less severe disease course for low-T2 patients.